Gambaran pemberian terapi pada pasien stroke dengan hemiparesis dekstra atau sinistra di Instalasi Rehabilitasi Medik RSUP Prof. Dr. R. D. Kandou Manado periode Januari-Maret tahun 2016 - Halim, Rusdyanto; Gesal, Joudy; Sengkey, Lidwina S. (e-CliniC, 2016)
Abstract: Stroke is one of the important problems in public health due to its morbidity, mortality, and high cost. In many countries in the world, stroke is the third leading cause of death after coronary heart disease and cancer. This study aimed to obtain the profile of medical rehabilitation treatment for stroke patients with hemipharesis. This was a retrospective descriptive study. Subjects were medical records of stroke patients with hemiparesis at Installation of Medical Rehabilitation at Prof. Dr. R. D. Kandou Hosipital Manado. The results showed that the medical rehabilitation treatment for stroke patients with hemiparesis in the period January-March 2016 in the Installation of Medical Rehabilitation at RSUP Prof. Dr. R. D. Kandou Manado was as follows: physiotherapy with infrared (31.402%), classis physical exercise (27.744%), active creative exercise (18.293%), daily activity adaptation (13.415%), therapeutic USD (2.449%), breathing exercise (2.134%), language exercise 0.610%), psychology rehabilitation (1.829%), proper body mechanisms (1.829%), and therapeutic medical social (0.305%). Keywords: stroke, hemiparesis, therapyÂ Abstrak: Stroke adalah salah satu masalah penting bagi kesehatan masyarakat karena memiliki angka kesakitan, angka kematian, dan biaya yang tinggi. Di banyak negara di dunia, stroke menduduki peringkat ketiga penyebab kematian sesudah penyakit jantung koroner dan kanker. Penelitian ini bertujuan untuk mendapatkan jenis-jenis penanganan rehabilitasi medik pada pasien stroke dengan hemiparesis. Jenis penelitian ini ialah deskriptif retrospektif. Subjek penelitian ialah data rekam medik pasien stroke dengan hemiparesis di Instalasi Rehabilitasi Medik RSUP. Prof. Dr. R. D. Kandou Manado. Hasail penelitian memperlihatkan pemberian terapi yang paling sering diberikan kepada pasien stroke dengan hemiparesis pada periode Januari-Maret 2016 di Instalasi Rehabilitasi Medik RSUP Prof. Dr. R. D. Kandou Manado ialah fisioterapi dengan pemberian infra merah (31,402%), latihan fisik klasik (27,744%), latihan aktif kreatif (18,293%), adaptasi AKS (13,415%), terapi USD (2,449%), latihan pernapasan (2,134%), latihan berbahasa (0,610%), rehabilitasi psikologi (1,829%), proper body mechanism (1,829%), dan terapi sosial medik (0,305%).Kata kunci: stroke, hemiparesis, terapi